Demokrasi Indonesia: Dari Masa Ke Masa - Hartuti Purnaweni (Centre for Public Policy and Management Studies, 2004)
The meaning and understanding of democracy along the histories of Indonesian government give specific meaning for the development of democracy in Indonesia. There are a lot of democracy paradox or democracy irony that happened in the orde lama era, orde baru era and reformasi era. The process and the development of democracy, finally face to face with the interest of power in the contexts of political trap that is true undemocratic. General election 2004 and Directly Regional Head Election 2005 are being momentum in the implementation of democratic governance, also challenge for political actors and community to raise cultural and structural democracy. By the way, Indonesian democracy still left some questions, that is, whether we prepare and capable to develop democracy without any irony or paradox.Kata kunci : paradox demokrasi, pilkada, membangun demokrasi